A Review of the Research on the Decision-Making Framework for Optimizing Rural Building Spatial Layout Based on Multi-Source Data Fusion: A Case Study of Hebei Province - HUI, ZHANG; Herman, Siti Sarah Binti (Journal of Posthumanism, 2025)
This paper systematically reviews the research progress of rural building spatial layout optimization decision-making based on multi-source data fusion, and discusses it with Hebei Province as a case study. Multi-source data fusion technology provides a new methodological framework for the study of rural building spatial layout, which can integrate multi-dimensional information such as remote sensing images, geographic information system data, socio-economic statistics and field survey data, and comprehensively analyze the characteristics of rural building space and its influencing factors. By reviewing relevant research results at home and abroad, this paper summarizes the application methods, evaluation systems and optimization strategies of multi-source data fusion in the study of rural building spatial layout, and constructs a comprehensive decision-making framework. Combined with the specific case of Hebei Province, the regional characteristics, existing problems and optimization directions of the rural building spatial layout in the region are analyzed, and a differentiated spatial layout optimization path based on multi-scenario analysis is proposed. The study shows that the decision-making framework based on multi-source data fusion can effectively support the scientific evaluation and optimization of rural building spatial layout, and provide theoretical basis and technical support for the implementation of the rural revitalization strategy and the improvement of rural living environment.